The Effect Of Financial Planning, Spending Habits, And Sources Of Income On Personal Financial Stability Through Self-Control As A Mediating Variable Among Students In The Faculty Of Economics And Business At The State University Of Makassar - Lilis Sampa; Syamsu Rijal; Hikmayani Subur; Marhawati Najib; Nurjannah (International Journal of Business and Quality Research, 2026)
This study aims to examine the impact of financial planning, spending habits, and sources of income on personal financial stability through self-control as a mediating variable among students at the Faculty of Economics and Business, Makassar State University. This study employed a quantitative method and surveyed 361 participants; Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to analyze the data. The results show that financial planning, spending habits, and income sources have a positive and significant effect on personal financial stability as well as on self-control. In addition, self-control was also found to have a positive and significant effect on personal financial stability. Furthermore, this study found that self-control acts as a significant mediating variable in the relationship between financial planning, spending habits, and income sources on personal financial stability.